Bioaccumulation of Copper and Zinc in Freshwater Crayfish (Astacus leptodactylus) Fed with Zebra Mussels (Dreissena polymorpha) Collected from Keban Dam Lake, Turkey - Aksu, Onder; Kucukgul Gulec, Azime; Demir, Veysel; Danabas, Durali; Yildirim, Numan; Ozcelik, Mehtap; Can, Erkan; Kocabas, Mehmet (Asian Journal of Chemistry, 2013)
This study is aimed to determine the bioaccumulation of copper and zinc in hemolymph of freshwater crayfish (Astacus leptodactylus) fed with zebra mussel (Dreissena polymorpha) collected from Keban Dam Lake. This is the first study on bioaccumulation of Cu and Zn in hemolymph of males and females of A. leptodactylus. The average concentrations of Cu and Zn in the hemolymph samples were found out as 0.54 and 35.07 ppm respectively for male and 0.42 and 15.59 ppm respectively for female control freshwater crayfish. The levels of Zn in the hemolymph of both male and female ones among control and diet groups were statistically significant (P < 0.05). The Cu levels among control and diet groups in female ones were statistically significant (P < 0.05) but not in the male ones (P > 0.05). The results of current study revealed that feed treatment with boiling was not effective at the levels of metal bioaccumulation in hemolymph. It was observed that this metal bioaccumulation is more related with sex differences.